2019
DOI: 10.1128/jcm.02012-18
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Pneumocystis jirovecii by Use of a New Simplified Nomenclature System Based on the Internal Transcribed Spacer Regions and 5.8S rRNA Gene of the rRNA Operon

Abstract: Genotyping based on internal transcribed spacer 1 (ITS1) and ITS2 of the rRNA operon has played an important role in understanding the transmission and epidemiology of Pneumocystis jirovecii, one of the major opportunistic pathogens in individuals with AIDS and other immunocompromised individuals. The widespread use of this typing system has resulted in several problems, including inconsistent genotype nomenclatures, difficult data transferability, and complicated interpretation of the length variation in mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The ITS region of P. jirovecii is the most polymorphic loci and widely used for genotyping [1]. In this study, we assessed and analyzed the P. jirovecii ITS genotype of 3 clinical samples from Shanxi province according to the new, simpli ed genotype nomenclature system [2]. We found ITS 4, ITS10 and ITS 59 genotypes, which were also identi ed in our previous study [2].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The ITS region of P. jirovecii is the most polymorphic loci and widely used for genotyping [1]. In this study, we assessed and analyzed the P. jirovecii ITS genotype of 3 clinical samples from Shanxi province according to the new, simpli ed genotype nomenclature system [2]. We found ITS 4, ITS10 and ITS 59 genotypes, which were also identi ed in our previous study [2].…”
Section: Discussionmentioning
confidence: 58%
“…The most prevalent genotype of ITS in Japan was Genotype 10 [24], which was observed in our study. In previous studies in China, Genotype 22 was most common in Beijing, Tianjin and Liaoning [2,15], whereas, Genotype 1 in Guangzhou [14]. However, it is di cult to accurately assess and statistically analyze the correlation between geographic diversity and P. jirovecii ITS genotypes based on the small sample size in this study.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As a result, eight genetic regions were explored in this study as potential loci which could be included in a global consensus scheme, by analysing their amplification ability and demonstrating their discriminatory power. The whole ITS region is widely reported to have the most variability within P. jirovecii and is highly useful when identifying and genotyping other invasive fungi [ 74 ]. Unfortunately, it also has been reported to have a high amplification failure when applied to P. jirovecii [ 59 ], which was also evident in the current study, as ITS1 alone and ITS1/2 regions showed to have the lowest amplification capability, unable to amplify and successfully sequence more than 50% of the studied isolates for either primer set.…”
Section: Discussionmentioning
confidence: 99%
“…The ITS1 and ITS2 regions have demonstrated the highest sequence variation among all loci of the rDNA gene cluster, as evident when sequenced as separate loci or in combination of the two regions (including the 5.8S gene), using nested-PCR techniques [ 3 ]. This has resulted in over 120 unique genotypes for both ITS regions reported and submitted to GenBank [ 74 ]. The ITS1 and ITS2 regions were chosen over the other genes in the rDNA gene cluster due to their superior discriminative power.…”
Section: Investigated Loci and Typing Schemesmentioning
confidence: 99%